Necesidad de reformar los artículos 215, 221, 224 y 225 de la Ley Orgánica De Transporte Terrestre, Tránsito y Seguridad Vial por cuanto el SOAT no cumple con el objetivo para lo que fue creado y por contravenir disposiciones de la Constitución de la República - Punina Aldás, Budther Marcelo (2015)
The Insurance Mandatory Transit Accident that appeared in Ecuador since 2008 and as you understands it sure was first born in Eastern countries for proliferase eventually all Continents but not all countries. Few countries in America that have this type of insurance especially in South America, Mandatory sure to say the criterion of Ecuadorian and foreign population does not meet the service for which it was created. Which is why there is an excess of disbelief on the part of society and there are few who benefit from the compensation provided by the Insurance Mandatory Transit Accident. The few who benefit are those who have twenty-four hours of time to walk in the diversity of procedures and / or those to be beneficiaries of the compensation of Insurance, spend more than they can perceive and that charging is regret having sought such compensation. But of course what gives it Statutory Accident insurance transit SOAT(Insurance Mandatory Transit Accident) are benefits that are not in the Constitution, such as compensation for temporary disability, permanent disability, loss of any part of your body, partial disability or total funeral expenses. The SOAT in a mode to tax by the government of the day and as you know Ecuador is a third world country that all Laws, Codes and Regulations, are faithful copies of other countries and today it has entered the era of SOAT also is a copy of other countries. Based on field research in the use of surveys and interviews can be determined conclusion is SOAT other in Ecuadorian society or should be modified. It’s just that, changing some of its articles what is proposed in this thesis prior to obtaining a law degree specifically Articles 215, 221, 224 and 225 of the Road Traffic Act, Land Transport and Road Safety because the SOAT not meet the purpose for which it was created and most importantly for contravening the provisions of the Constitution and based on the criteria of the Ecuadorian population obtained in the investigation, it would be best this the definitive abolition of Insurance Mandatory Traffic Accident